2021
DOI: 10.3233/jnd-200518
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Peripheral Neuropathies

Abstract: Objectives: Generally, neuropathies of peripheral nerves are a frequent condition (prevalence 2–3%) and most frequently due to alcoholism, diabetes, renal insufficiency, malignancy, toxins, or drugs. However, the vast majority of neuropathies has orphan status. This review focuses on the etiology, frequency, diagnosis, and treatment of orphan neuropathies. Methods: Literature review Results: Rareness of diseases is not uniformly defined but in the US an orphan disease is diagnosed if the prevalence is <1:20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 118 publications
(87 reference statements)
0
26
0
14
Order By: Relevance
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [ 17 , 41 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 85%
See 4 more Smart Citations
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [ 17 , 41 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 85%
“…In this line, reductions of the SNAPs of >11.5% in the median nerve between baseline and four cycles of OXA (odds ratio = 5.603, p = 0.031) and of >22.5% in the sural nerve between four and eight cycles of chemotherapy (odds ratio = 5.603, p = 0.031) were independently associated with the risk of developing severe OXAIPN [ 63 ]. However, very recently, negative results were obtained in another study evaluating the role of the sural nerve after administering 25% or 50% of the planned OXA dose in predicting the occurrence of clinically significant OXAIPN in 55 CRC patients [ 59 ]. The assessment of sural nerve instead dorsal sural ( Figure 2 ), and the size of the study could underlie these negative findings.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 99%
See 3 more Smart Citations